2013
DOI: 10.1080/09540121.2012.749339
|View full text |Cite
|
Sign up to set email alerts
|

Quality of relationship and sexual risk behaviors among HIV couples in Lusaka, Zambia

Abstract: Relationship quality and partner dynamics provide important insights into understanding sexual behavior within HIV sero-positive and -discordant couples. Individuals in long-term partnerships may be vulnerable to HIV/STI infection within their relationships due to misperceptions of their partners risk behaviors and potential concurrent (e.g., extramarital, non-primary) sexual partnerships. This study sought to examine relationship quality among HIV sero-positive and – discordant couples in Zambia, and its asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…We find dual protection is determined by partner's HIV status. There is a growing body of literature that links the ability of women living with HIV to use condoms and contraception to a positive relationship context (i.e., quality of relationship, partner dynamics, and communication) [ 39 – 41 ]. Our study finds that women with HIV-serodiscordant partners report the most consistent condom use, followed (in order) by women who do not know their partners' HIV status, and women with HIV-seroconcordant partners.…”
Section: Resultsmentioning
confidence: 99%
“…We find dual protection is determined by partner's HIV status. There is a growing body of literature that links the ability of women living with HIV to use condoms and contraception to a positive relationship context (i.e., quality of relationship, partner dynamics, and communication) [ 39 – 41 ]. Our study finds that women with HIV-serodiscordant partners report the most consistent condom use, followed (in order) by women who do not know their partners' HIV status, and women with HIV-seroconcordant partners.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern of results is consistent with findings from a study in Zambia that found that communication about condoms was associated with safer sexual behavior in couples. 33 Similarly, a study in a township near Cape Town, South Africa also found that discussing condom use with sexual partners was associated with increased condom use. 37 …”
Section: Discussionmentioning
confidence: 95%
“…27 Communication about condom use is also emphasized as an important factor for reducing exposure to HIV and several studies have tied such communication to increased condom use in men. 2833 Although public health researchers have long recognized the importance of fatherhood in the promotion of optimum health and the reduction of health problems among men, 34 little is known about the relation between having a child and HIV sexual risk behavior among men. This study was guided by the hypothesis that older age, religiosity, having children, and communication about condoms are associated with South African men’s sexual risk behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Couple sexual communication self-efficacy (SCSE), defined as a couple’s confidence in their ability to communicate about sexual risk reduction, has the potential to be a key leverage point for HIV prevention interventions for this high risk group (Matseke, Peltzer, Mchunu, & Louw, 2012; Vamos et al, 2013). Past research in this area has typically focused on the impact of condom negotiation self-efficacy on consistent condom use at the individual level (Onoya et al, 2011; Sayles et al, 2006).…”
Section: Introductionmentioning
confidence: 99%